Case-control Study of the Frequency of Thrombophilic Disorders in Couples with Late Foetal Loss and no Thrombotic Antecedent - Gris, Jean-Christophe; Quéré, Isabelle; Monpeyrou, Françoise; Mercier, Eric; Ripart-Neveu, Sylvie; Tailland, Marie-Laure; Hoffet, Méderic; Berlan, Jacques; Daurès, Jean-Pierre; Marès, Pierre (Thrombosis and Haemostasis, 1999)
Background: Women with familial thrombophilia have an increased risk of still birth. We postulated that the presence of asymptomatic risk factors for venous thrombosis might be a risk factor for late foetal loss. Methods: We performed a case-control study on the prevalence of heritable thrombophilic defects, of antiphospholipid-related markers and of the C677T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene in patients with at least one episode of late unexplained foetal loss and in control women with successful pregnancies. Partners of cases and controls were also studied. Written conclusions of the pathological examination of the placentas, when available, were also reviewed. Results: We found at least one positive biological risk factor for venous thrombosis in 21.1% of the patients and in 3.9% of the controls (p <10–4). In women, the crude odds ratio for still birth associated with any positive biological risk factor for venous thrombosis was 5.5, 95% confidence interval (95%CI) [3.4-9.0]. No difference was found between partners of cases and controls (5.2% and 4.7%). Using conditional logistic regression analysis, 4 adjusted risk factors for still birth remained: protein S deficiency, positive anti β2 glycoprotein I IgG antibodies, positive anticardiolipin IgG antibodies and the factor V Leiden mutation. The C677T mutation in the MTHFR gene was not an individual risk factor but an homozygous genotype was strongly associated with the former 4 risk factors (16.8% of patients vs. 0.9% of controls). In women with such associations, still births always occurred in absence of folic acid supplementation during pregnancy. Available conclusions of pathological analysis of placentas were found to have a very high proportion of “maternal vascular disease of the placenta” in patients with at least one positive risk marker for thromboembolism, specially in case of association with the C677T MTHFR homozygous genotype, compared to patients with negative markers (p <10–4). Conclusions: Late foetal loss, through placenta thrombosis, may sometimes be the consequence of a maternal multifactorial prothrombotic state associating traditional heritable or acquired thrombosis risk factors to conditions predisposing to an acute mild hyperhomocysteinaemia (coexistence of a genetic predisposition with late pregnancy-related increased folate needs).